2018
DOI: 10.1088/1361-6501/aaf2b7
|View full text |Cite
|
Sign up to set email alerts
|

Critical review of electrocardiography measurement systems and technology

Abstract: Electrocardiography (ECG) is widely used in clinical practice, for example to diagnose coronary artery disease or the cause of chest pain during a stress test, while the patient is running on a treadmill. Ambulatory ECG monitoring is used for long term recording of ECG signals, while the patient carries out his/her daily activities. Artefacts in ECG are caused by the patient’s movement, moving cables, interference from outside sources, electromyography (EMG) interference and electrical contact from elsewhere o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
44
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 102 publications
1
44
0
Order By: Relevance
“…In addition, different concentrations of GelMA hydrogels were prepared and their performances in constructing unique shape were assessed. Results showed that a series of GelMA hydrogel with different pregel concentrations (10,15, and 20 wt%) could form unique shape easily and consistently (Figure S7, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, different concentrations of GelMA hydrogels were prepared and their performances in constructing unique shape were assessed. Results showed that a series of GelMA hydrogel with different pregel concentrations (10,15, and 20 wt%) could form unique shape easily and consistently (Figure S7, Supporting Information).…”
Section: Resultsmentioning
confidence: 99%
“…Therefore as in the proposed case, forming the MFP with hard epoxy avoids the loss of the liquid during insertion process. This can also be compatible to the human's skins having large range of young's modulus 9 . The very performing liquid handling of the MFP is also partly supported by the large surface opening area (1.32mm 2 thus 76% of 4 sides of pyramid) of the MFP allowed facile liquid absorption and release.…”
mentioning
confidence: 80%
“…Statistical reports indicated that the leading cause of death in the world comes from cardiovascular diseases [9,20]. The World Health Organization (WHO) reported that the total number of deaths from cardiovascular diseases in 2012 was approximately 17.5 million, compared with 17.7 million in 2015, and this number has been increasing every year [1,3,9].…”
Section: Introductionmentioning
confidence: 99%
“…Hence, monitoring ECG and performing automatic diagnosis become particularly important. In cardiology, the electrical actions of a human's heart are simply and painlessly recorded by electrocardiogram (ECG) via single or multiple-lead detections [8,20]. The real-time ECG sequence of a patient represents one of the most useful clinical diagnostic features on cardiovascular diseases, reflecting the electrophysiological activity of cardiac excitement, and indicating great importance on the aspects of basic heart functions and related pathological research [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation